What to do when you worry too much : a kid's guide to overcoming anxiety - Huebner, Dawn.; Matthews, Bonnie, 1963- (Washington, D.C. : Magination Press, 2006)
"Teaches school-age children cognitive-behavioral techniques to reduce and overcome anxiety, fears, and worry, through writing and drawing activities and self-help exercises and strategies. Includes introduction for parents"--Provided by publisher.
Are you growing worries? -- What is a worry? -- How do worries get started? -- Making worries go away -- Spending less time on worries -- Talking back to worries -- Re-setting your system -- Keeping worries away -- You can do it!
edited hb 2015-06-16
Keywords: Worry in children -- Juvenile literature; Anxiety in children -- Juvenile literature; Worry; Anxiety